THE SERVICE PERFORMANCE EVALUATION OF MADIUN TRAIN STATION - Silfi Galuh Navitasari; Akhmad Hasanuddin; Nunung Nuring Hayati; Sonya Sulistyono (Universitas Jember, 2019)
Transportation is a community’s needs at this time. In the development of transportation, transportation modes which is developing as a solution problems of time efficiency, safety, transportation capacity, and estimate costs for the population of Indonesia. For the population of Indonesia, especially the people in Madiun, railway facilities are transportation modes that energy saved and have a better level of safety than other transportation. This study discusses safety, security, reliability, convenience, simplicity, and equality of SPM which is consist of physical variables indicator, reliability, response, empathy, and concern. The research sample was participants in the departure place at Madiun Train Station. The samples did by random sampling method. Data collection uses a questionnaire which distributed directly for 400 questionnaires. Analysis method uses the Important Performance Analysis (IPA) method with validity testing using Bivariate Pearson (Product Moment Pearson) and reliability testing using Cronbach Alpha (ɑ) statistical test. The results of service quality and facility performance researches showed 94.44% of availability and 88.89% of fulfilment at Madiun Station according to PM.48 of 2015. Whereas the results of conformity and gap researches showed the assessment integrity accordance to concerns and expectations of the highest GAP service users - 0.90 according to variable indicator. Transportasi merupakan kebutuhan masyarakat pada saat ini. Dalam perkembangan transportasi, moda transportasi yang berkembang sebagai solusi permasalahan tentang efisiensi waktu, keselamatan, kapasitas penumpang, dan estimasi biaya bagi penduduk Indonesia. Bagi penduduk Indonesia khususnya masyarakat di Madiun, sarana kereta api adalah moda transportasi yang hemat energi dan tingkat keselamatan yang lebih baik dibandingkan transportasi lain. Penelitian ini bertujuan menguji keselamatan, keamanan, kehandalan, kenyamanan, kemudahan, dan kesetaraan terhadap SPM berupa indikator variabel fisik, keandalan, tanggapan, empati, dan peduli. Sampel penelitian ini adalah penumpang pemberangkatan di Stasiun Madiun. Sampel dilakukan dengan metode acak. Pengumpulan data berupa kuesioner yang disebarkan secara langsung sebanyak 400 kuesioner. Metode analisis menggunakan metode Importance Performance Analysis (IPA) dengan uji validitas menggunakan Bivariate Pearson (Product Moment Pearson) dan uji reliabilitas menggunakan uji statistic Cronbach Alpha (ɑ). Hasil penelitian kualitas kinerja pelayanan dan fasilitas menunjukkan ketersediaan sebesar 94,44 % dan keterpenuhan sebesar 88,89 % di Stasiun Madiun sesuai PM.48 Tahun 2015. Sedangkan, hasil penelitian kesesuaian dan kesenjangan menunjukkan bobot penilaian sesuai kepentingan dan harapan pengguna jasa senilai GAP tertinggi -0,90 sesuai indikator variabel.